2013
DOI: 10.4319/lom.2013.11.101
|View full text |Cite
|
Sign up to set email alerts
|

Cleaning methods for the isotopic determination of diatombound nitrogen in non‐fossil diatom frustules

Abstract: Ground-truthing the stable isotope ratio of diatom frustule-bound organic nitrogen (N) as a paleoceanographic proxy of phytoplankton nutrient consumption calls for studies of modern diatoms from cultures and the field. This work has been hindered by the lack of a method to prepare fresh diatom material, which has significant geochemical differences from sedimentary fossil diatom, for analysis. We tested and compared the performance of five oxidative treatment protocols in cleaning fresh diatom frustules of ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 31 publications
2
18
0
Order By: Relevance
“…The δ 15 N db difference that characterizes the centric and pennate diatom assemblages may indicate (1) a difference in seasonality or depth habitat, as it affects the δ 15 N of the available nitrate, (2) differences in the dominant form of N assimilated (i.e., nitrate or recycled ammonium) [ Fawcett et al ., ], or (3) physiological differences that result in a different δ 15 N db /diatom biomass δ 15 N relationship [ Horn et al ., ; Morales et al ., ]. Regarding the last, if the centric‐pennate δ 15 N db difference were solely due to differences in fundamental biosynthesis pathways as they impact the δ 15 N relationship between the biomass N of a diatom and its frustule‐bound N, then a constant interassemblage difference would be expected over time.…”
Section: Interpretation and Discussionmentioning
confidence: 99%
“…The δ 15 N db difference that characterizes the centric and pennate diatom assemblages may indicate (1) a difference in seasonality or depth habitat, as it affects the δ 15 N of the available nitrate, (2) differences in the dominant form of N assimilated (i.e., nitrate or recycled ammonium) [ Fawcett et al ., ], or (3) physiological differences that result in a different δ 15 N db /diatom biomass δ 15 N relationship [ Horn et al ., ; Morales et al ., ]. Regarding the last, if the centric‐pennate δ 15 N db difference were solely due to differences in fundamental biosynthesis pathways as they impact the δ 15 N relationship between the biomass N of a diatom and its frustule‐bound N, then a constant interassemblage difference would be expected over time.…”
Section: Interpretation and Discussionmentioning
confidence: 99%
“…Physically separated diatom samples were cleaned using (1) a preliminary oxidation of external organic matter using ~5 ml of 18 M sulfuric acid, ~15 ml saturated potassium permanganate, and ~15 ml saturated oxalic acid [ Hasle and Fryxell , ], (2) a reductive cleaning step using a heated (80°C for 1 h) sodium dithionite solution to remove adsorbed metals, and (3) two final 1 h oxidations of organic matter using a weak (~35%) and then strong (72%) solution of perchloric acid in a 100°C water bath [ Horn et al, ; Morales et al, ]. Splits of the clean, dry diatom samples were dissolved and the organic N oxidized to nitrate in a 0.22 M potassium persulfate and 1.5 M sodium hydroxide solution in an autoclave at 121°C for 20 min [ Bronk et al, ; Robinson et al, ].…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that Thalassiosira pseudonana frustules contained hydrocarbons, protein and lipids after a H2O2 treatment [35] . Furthermore, H2O2 treatment removed more elements from the frustules than SDS/EDTA [34] , and facilitated the access to N embedded in the biosilica [33] . These observations may influence the choice of cleaning methods for frustules that are subjected to elemental analyses.…”
Section: Sem/eds and Element Analysismentioning
confidence: 99%
“…acids, bleaching, oxidising or denaturation functions from different chemicals, and thermal treatment. There are few systematic studies with comparisons of different cleaning methods [30] , [31] , [32] , [33] , [34] . Here, a comparative study of two frustule cleaning methods is presented, using carefully described cleaning protocols based on established cleaning principles [35] .…”
Section: Introductionmentioning
confidence: 99%